New fluorescent imaging technics in gastrology - Sosna, Barbara; Bartusik-Aebisher, Dorota; Cieślar, Grzegorz; Kawczyk-Krupka, Aleksandra; Latos, Wojciech (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. There is a need to develop a new imaging technique in medicine. Gastroenterology is the branch of medicine focused on the digestive system and its disorders therefore for this branch is needed to detect all problems affecting the gastrointestinal tract. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of this article is to complete discuss the possibility of the new fluorescent imaging technics in gastrology to use innovative screening to identify individuals at an early stage. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. We discuss here imaging techniques such as include x-rays, computed tomography, scans, and magnetic resonance imaging in gastrology. Spectroscopy is the study of the formation and interpretation of spectra resulting from the interaction of all types of radiation on matter understood as a community of atoms and molecules. Various spectroscopic techniques are obtained by combining different types of radiation with different ways of its interaction with the test sample. They provide the opportunity to obtain detailed information about the tested substance – from its atomic composition, through its chemical structure, to its surface structure. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literatue. The tissue fluorescence spectrum can be obtained by: (1) autofluorescence, or natural or primary fluorescence, i.e. by direct irradiation of the tissue with laser radiation (laser-induced fluorescence – LIF) and (2) photodynamic diagnosis (PDD), where spectrum analysis is preceded by systemic or local administration of the photosensitizer. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The use of fluorescence imaging in colon cancer patient has potential to improve quality of treatment and diagnosis.